Recharge sources and hydrogeochemical evolution of groundwater in alluvial basins in arid central Australia - Vanderzalm, J.L.; Jeuken, B.M.; Wischusen, J.D.H.; Pavelic, Paul; Le Gal La Salle, C.; Knapton, A.; Dillon, P.J. (Elsevier, 2011)
It is necessary to define the role of various sources of recharge in the surficial alluvial aquifer system in arid Alice Springs in central Australia, for future management of water resources in the region. Multiple sources of natural recharge include infiltration from ephemeral stream flow in the Todd River; groundwater throughflow between connected alluvial basins; regional groundwater flow from the underlying Tertiary aquifer; and diffuse recharge. In addition treatment, storage and irrigation reuse of Alice Springs' waste water has resulted in additional recharge of effluent, via infiltration. Water resource management plans for the region include effluent reuse through Soil Aquifer Treatment (SAT) within one of the connected alluvial basins, with the purpose of managing the excess waste water overflows while also supplementing groundwater resources for irrigation and protecting their quality. Hydrogeochemical tracers, chloride and the stable isotopes of water, were used in a three-member mixing model to define and quantify the major recharge sources. The mixing model was not sensitive enough to quantify minor contributions from effluent in groundwater that were identified only by an evaporated isotopic signature. The contribution of the multiple recharge sources varied spatially with proximity to the recharge source; with Todd River, effluent and Town Basin throughflow contributing to the Inner Farm Basin groundwater. The Outer Farm Basin was largely influenced by the Todd River, the Inner Farm Basin throughflow and the older Tertiary aquifer. While Inner Farm groundwater throughflow contains an effluent component, only Outer Farm Basin groundwater near the interface between the two basins clearly illustrated an effluent signature. Aside from this, effluent recharge was not evident in the Outer Farm Basin, indicating that past unmanaged recharge practices will not mask signs of Managed Aquifer Recharge through the Soil Aquifer Treatment (SAT) operation. The long-term impact of effluent recharge is a shift from sodium and calcium as co-dominant cations in the groundwater, as evident in the Outer Farm Basin, to dominance by sodium alone, as typical for the Inner Farm Basin.